DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mayangsari, Dewi; Wahyuningsih, Panca (STIE PENA, 2022)
This study aims to determine whether company size, debt policy, and profitability affect firm value. Sampling was carried out by purposive sampling method, which is a sampling method with certain criteria. The type of research used is quantitative. The results of this study indicate that company size has a negative and insignificant effect on firm value, debt policy has a positive and significant effect on firm value, and profitability has a negative and insignificant effect on firm value. Company size, debt policy, and profitability jointly or simultaneously have a significant effect on company value.Keywords: Company Size, Debt Policy, Profitability, Value CompanyThis study aims to determine whether company size, debt policy, and profitability affect firm value. Sampling was carried out by purposive sampling method, which is a sampling method with certain criteria. The type of research used is quantitative. The results of this study indicate that company size has a negative and insignificant effect on firm value, debt policy has a positive and significant effect on firm value, and profitability has a negative and insignificant effect on firm value. Company size, debt policy, and profitability jointly or simultaneously have a significant effect on company value. Keywords: Company Size, Debt Policy, Profitability, Value Company